The Influence Of Pd Nanoparticle Size On Pd/TiO2 Catalysts For Cinnamaldehyde Hydrogenation Reaction - Abdullah, Norli; Bahruji, Hasliza; Che Ros, Fadhlina; Mohamad, Imran Syakir (Malaysian Society of Analytical Sciences, 2020)
Palladium nanoparticles (PdNP) supported onto the anatase phase of TiO2 were successfully synthesised using a colloidal method. This synthesis method involved the reduction of K2PdCl4 solution by NaBH4 at different temperatures (1, 25, 50, 75oC) and stabilised with PVA ligand. Transmission electron microscope (TEM) was used to determine the particle size of PdNP on the TiO2. Colloidal synthesis at 1oC and 25oC produced PdNP with less than a 3 nm diameter, whereas when the synthesis temperatures were higher than 25oC, PdNP were produced with a size larger than 4 nm. The catalytic activity of Pd/TiO2 was significantly improved when palladium (Pd) was produced at 1oC with high selectivity towards the hydrogenation of cinnamaldehyde to hydrocinnamaldehyde. The conversion and selectivity trends from the cinnamaldehyde hydrogenation reaction demonstrated the influence of Pd nanoparticle size to provide active sites for the reduction of C=C and C=O bonds. Pd with a diameter of 2.58 nm favoured hydrogenation of C=C bond to produce high selectivity towards hydrocinnamaldehyde, meanwhile a large Pd diameter > 4 nm allowed simultaneaous reduction of C=C and C=O bonds to give comparable selectivity between hydrocinnamaldehyde and hydrocinnamylalcohol.